Developing novel synbiotic low‐fat yogurt with fucoxylogalacturonan from tragacanth gum: Investigation of quality parameters and Lactobacillus casei survival. Issue 8 (29th June 2020) - Ghaderi‐Ghahfarokhi, Maryam; Yousefvand, Amin; Ahmadi Gavlighi, Hassan; Zarei, Mehdi; Farhangnia, Peyman
Abstract: Tragacanth gum (TG) displayed a prebiotic activity, but its application was restricted due to high viscosity and deterioration of organoleptic and textural characteristics of food. In this study, TG was depolymerized by Pectinex Ultra Color enzyme followed by membrane separation (30 kDa) to get pectinase hydrolyzed fraction of tragacanth gum (PHFTG) with molecular weight more than 30 kDa. The average molecular weight of PHFTG was 147.7 ± 11.5 g/mol having a fucoxylogalacturonan structure. The prebiotic activity was tested using PHFTG, TG, and inulin as a carbon source. The results showed that the count of Lactobacillus casei in PHFTG‐ and inulin‐supplemented media increased significantly during the 48‐hr fermentation ( p  < .05). Five batches of low‐fat set yogurts were prepared by the following formulation: Control (without both L. casei and prebiotic), LC‐Cont (containing L. casei ), LC‐PHFTG (containing L. casei  + 0.5% PHFTG), LC‐TG (containing L. casei  + 0.05% TG), and LC‐In (containing L. casei  + 0.5% inulin), and L. casei population and physicochemical properties were monitored during 21‐day storage at 4°C. The number of L. casei remained highly acceptable (8.54–8.61 log CFU/g) during 7–21 days of storage in LC‐PHFTG. LC‐In and LC‐PHFTG presented significantly lower syneresis and higher sensory acceptability than LC‐Cont and Control during storage ( p  < .05). LC‐TG displayed weaker body and texture, lower sensory acceptability, and higher syneresis than other samples. This study provides support for expanding the utilization of PHFTG as a potential prebiotic and fat replacer in non‐ or low‐fat dairy products with satisfactory sensory quality. Abstract : Tragacanth gum was depolymerized by Pectinex Ultra Color enzyme followed by membrane separation (30 kDa) to get pectinase hydrolyzed fraction of tragacanth gum (PHFTG) with molecular weight more than 30 kDa. The highest Lactobacillus casei counts were observed on day 7 for all yogurts. Surprisingly, the counts of L. casei were always higher than 8.5 log CFU/g in LC‐PHFTG sample from day 7, and after that, the counts seemed to be stagnant. The L. casei count of LC‐In yogurts appeared significantly lower than LC‐PHFTG on day 21 ( p  < .05).